Pengenalan Sumber Daya Alam Dengan Kandungan Antioksidan Tinggi Dalam Rangka “Pencegahan Penyakit Degenaratif” - Nuning Nurcahyani; Endah Setyaningrum; Endang L Widiastuti; Indriyani (AMMA : Jurnal Pengabdian Masyarakat, 2024)
This activity was carried out in Banjar Agung Udik Village, Tanggamus, Lampung. This activity aims to provide knowledge about the benefits of antioxidants from surrounding natural resources in order to increase awareness of the importance of health among the community to prevent degenerative diseases. Banjar Agung Udik village is an area rich in natural resources. Most of the people are vegetable and fruit farmers, gardeners, and raise fish in ponds to meet their daily needs. One of the weakness of the local community is that they still have limited knowledge about the importance of natural resources that are rich in antioxidants and are beneficial for health, namely as preventing degenerative diseases. Therefore, training on the benefits of antioxidants from surrounding natural resources is very necessary to increase awareness of the importance of health through preventing degenerative disease among the people of Banjar Agung Udik. With the addition of this training, the knowledge and insight of the Banjar Agung Udik village community regarding the introduction of natural resources with high oxidant content as a means of preventing degenerative disease has increased. Apart from that, people are able to explain the benefits of natural resources with high antioxidant content for preventing degenerative disease.